The Army in Cromwellian England, 1649-1660 - Reece, Henry (Oxford University Press, 2013)
From 1649-1660 England was ruled by a standing army for the only time in its history. In The Army in Cromwellian England Henry Reece describes, for the first time, the nature of that experience, both for members of the army and for civilian society.